(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article focuses on the development of the banking sector in a digital economy, the transformation of traditional banking products and services, as well as the assessment of the weak and strong positions of banks in their competitive strategies in the market in relation to other financial intermediaries. The article notes that the development of fintech intermediaries leads banks to the need to constantly improve their infrastructure and risk management systems, adapt to rapid changes in the technology of traditional operations, change their market behavior strategies and approaches to assessing their competitive capabilities